Effect ofintercrops and planting pattern on incidence of anthracnose, productivity potential and economics of greater yam (Dioscorea alata)* - NEDUNCHEZHIYAN, M; BYJI, G; NASAKR, S K (The Indian Journal of Agricultural Sciences, 2011)
An investigation was carried out during 2001-02 and 2002 to find out the effect of intercrops and planting pattern on incidence of anthracnose, productivity potential and economics of greater yam (Dioscorea alata L.) cultivation. Maize (Zea 1nays L.) as an intercrop reduced about 62.3 and 57 0/0 ofanthracnose incidence over the sole yam during the year 200 I-02 an 2002-03 respectively and it was found better.